Interceptive Treatment of Anterior Crossbite: Case series - Teresa Pinho (Nascer e Crescer, 2018)
The aim of this paper was to assess changes of the lower cervical-facial proportion for child patients with anterior crossbites (AXB) in interceptive treatment using composite ramps. Intra-oral and facial lateral profile of seven children (4.5–9 years old) during interceptive treatment of anterior dental (ADXB), functional (AFXB) and skeletal crossbites (ASXB) were used. For ADXB/AFXB, a composite ramp was used; posterior bite composite or sectional fixed braces were added when necessary. In ASXB a facemask and/or composite ramp and brackets were used. AXB of all patients was improved. ADXB/AFXB (cases 1–4) were associated with an increased cervical-facial portion (posterior rotation of the mandible), while ASXB/AFXB (cases 5–7) were associated with a reduced proportion (anterior mandible rotation). Regardless of AXB type, a ramp composite promoted an increase in the vertical dimension and consequently posterior rotation of the mandible, thus worsening the cervicalfacial proportion in ADXB/AFXB and improving it in ASXB/AFXB.